INOVASI PANGAN LOKAL BERBASIS DAUN KELOR SEBAGAI UPAYA PENCEGAHAN STUNTING PADA BALITA - Nelly Nugrawati; Nur Ekawati; Ayu Wijaya; Andi Muhammad Adam (Institut Kesehatan Yarsi Mataram, 2026)
Stunting remains one of the chronic nutritional problems among toddlers that requires preventive efforts through the utilization of highly nutritious local food sources. Moringa leaves (Moringa oleifera) are a local food rich in protein, iron, calcium, vitamins, and antioxidants, making them potentially beneficial in supporting the nutritional needs of toddlers. This community service activity aimed to improve the knowledge and skills of mothers with toddlers through local food innovations based on moringa leaves in the form of moringa nuggets and moringa pudding as an effort to prevent stunting among toddlers in Tonasa Village, Gowa Regency. The activity methods included coordination with village authorities and health cadres, participant identification, implementation of a knowledge pre-test, education regarding stunting and the benefits of moringa leaves, demonstrations and training on moringa-based food processing, distribution of recipe leaflets, implementation of a post-test, and evaluation of the application of moringa-based foods within toddlers’ families. A total of 15 participants were involved in the activity, comprising 10 mothers of toddlers and 5 Posyandu cadres. The results showed an increase in participants’ knowledge, where the proportion of participants with good knowledge increased from 27% during the pre-test to 87% during the post-test. Participants’ skills in processing moringa leaves into nutritious food also improved, from 20% to 80% in the good category. In addition, most participants stated that their toddlers liked the moringa nugget and moringa pudding products provided during the training and had started to apply them as additional family meals. This local food innovation based on moringa leaves was considered effective, economical, easy to implement, and has the potential to support sustainable stunting prevention efforts among toddlers at the community level.